2022
DOI: 10.3389/fimmu.2021.811364
|View full text |Cite
|
Sign up to set email alerts
|

Co-Expression of miR155 or LSD1 shRNA Increases the Anti-Tumor Functions of CD19 CAR-T Cells

Abstract: Chimeric antigen receptor (CAR) T cells targeting CD19 antigen have produced remarkable clinical outcomes for cancer patients. However, identifying measures to enhance effector function remains one of the most challenging issues in CD19-targeted immunotherapy. Here, we report a novel approach in which a microRNA (miRNA) or short-hairpin RNA (shRNA) cassette was integrated into CAR-expressing retroviral vectors. Using this system, we generated anti-CD19 CAR-T cells co-expressing miR155 or LSD1 shRNA and found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…However, because the occurrence and development of cancers are very complex biological processes, all oncogenic factors or pathways mediated by LSD1 could not be described in this review. Some examples include SOX2, which maintains cancer cell stemness; sex hormone receptors (AR and ER); the transcriptional repressor ZNF516; retinoic acid-related orphan receptor alpha (RORα); aryl hydrocarbon receptors; ubiquitin-specific protease 28 and miRNAs ( Park et al, 2016 ; Bai et al, 2017 ; Khanal et al, 2017 ; Kim et al, 2017 ; Li et al, 2017 ; Macheleidt et al, 2018 ; Cuyàs et al, 2020 ; Yu et al, 2020 ; Zhang et al, 2021 ). However, the detailed mechanisms of LSD1 underlying carcinogenesis remain unclear and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because the occurrence and development of cancers are very complex biological processes, all oncogenic factors or pathways mediated by LSD1 could not be described in this review. Some examples include SOX2, which maintains cancer cell stemness; sex hormone receptors (AR and ER); the transcriptional repressor ZNF516; retinoic acid-related orphan receptor alpha (RORα); aryl hydrocarbon receptors; ubiquitin-specific protease 28 and miRNAs ( Park et al, 2016 ; Bai et al, 2017 ; Khanal et al, 2017 ; Kim et al, 2017 ; Li et al, 2017 ; Macheleidt et al, 2018 ; Cuyàs et al, 2020 ; Yu et al, 2020 ; Zhang et al, 2021 ). However, the detailed mechanisms of LSD1 underlying carcinogenesis remain unclear and warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia-inducible factor 1-alpha (HIF-1α) is a key protein that regulates the expression and synthesis of cytokines and growth mediators in cells during hypoxia (Yang et al, 2021c). It plays an essential role in the formation of tumor blood vessels and the proliferation, metastasis, invasion, apoptosis, energy metabolism, and drug resistance of tumor cells (Li G. et al, 2021). The expression of HIF-1α is positively correlated with the malignancy and poor prognosis of cancers.…”
Section: Hypoxia-inducible Factor-1αmentioning
confidence: 99%
“…78,79 However, a new study integrated miR-155 into the vector of anti-CD19 CAR-T cells and reported an increase in the anti-tumour functions against lymphoma in vivo and in vitro due to induction of interferon-γ (IFN-γ) and cytolytic activity of CAR-T cells. 80 These results suggest different roles for miR-155 in immune cells and tumour cells. In other words, the expression of miR-155 in tumour tissue is a negative biomarker that predicts poor prognosis and drug resistance, but in T cells, it is a positive biomarker that predicts good response to CAR-T-cell therapy.…”
Section: Predictive Ncrna Biomarkers For Response To Car-t-cell Therapymentioning
confidence: 99%
“…Other studies reported oncogenic function of miR‐155 in breast and lung cancers 78,79 . However, a new study integrated miR‐155 into the vector of anti‐CD19 CAR‐T cells and reported an increase in the anti‐tumour functions against lymphoma in vivo and in vitro due to induction of interferon‐γ (IFN‐γ) and cytolytic activity of CAR‐T cells 80 . These results suggest different roles for miR‐155 in immune cells and tumour cells.…”
Section: Predictive Nrna Biomarkers For Response To Immunotherapy In ...mentioning
confidence: 99%
“…Besides MyD88/CD40, in a murine model of B cell malignancies, miR155 overexpression together with Lysine-specific demethylase 1 (LSD1) knocking down can induce rapid expansion of CD19-CAR-T cells and improve their antitumor function (although the detailed mechanism remains unclear) ( 99 ).…”
Section: Approaches To Prolong the Persistence Of Car-t Cellsmentioning
confidence: 99%